2008
DOI: 10.1002/jcc.20899
|View full text |Cite
|
Sign up to set email alerts
|

A reactive bond orbital investigation of the Diels‐Alder reaction between 1,3‐butadiene and ethylene: Energy decomposition, state correlation diagram, and electron density analyses

Abstract: The reactive bond orbital (RBO) method (Hirao, Chem Phys Lett 2007, 443, 141) is extended and applied to the Diels-Alder reaction between 1,3-butadiene and ethylene, with the aim of understanding the nature of their interaction. The roles of distortion, electrostatic, exchange, polarization, and charge transfer (CT) interaction energies at the transition state of the reaction are evaluated by means of RBO energy decomposition analysis. The effects of the hypothetical interactions on electron density redistribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…1). [1][2][3][4][5][6][7] Previous isotope studies indicate a preference for the concerted mechanism, as supported by the Woodward and Hoffmann rules for pericyclic reactions, [8] however, the formation of a small quantity of a second product in which the isotope labels are scrambled suggests another mechanism involving biradical intermediates. [2,9,10] The biradical transition states consist of the stepwise and asynchronous biradical pathways where the stepwise involves the formation of one bond followed by the diene or dienophile rearranging itself such that the second bond can form.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…1). [1][2][3][4][5][6][7] Previous isotope studies indicate a preference for the concerted mechanism, as supported by the Woodward and Hoffmann rules for pericyclic reactions, [8] however, the formation of a small quantity of a second product in which the isotope labels are scrambled suggests another mechanism involving biradical intermediates. [2,9,10] The biradical transition states consist of the stepwise and asynchronous biradical pathways where the stepwise involves the formation of one bond followed by the diene or dienophile rearranging itself such that the second bond can form.…”
Section: Introductionmentioning
confidence: 93%
“…Two mechanisms for the Diels–Alder reactions of 1,3‐butadiene with both ethene and itself have been proposed consisting of concerted and two‐step biradical cycloadditions (Fig. ) . Previous isotope studies indicate a preference for the concerted mechanism, as supported by the Woodward and Hoffmann rules for pericyclic reactions, however, the formation of a small quantity of a second product in which the isotope labels are scrambled suggests another mechanism involving biradical intermediates .…”
Section: Introductionmentioning
confidence: 97%
“…The PES and the transition state structures are displayed in Figure 3, and energetic results are summarized in Table S2. The first step could be a Diels-Alder type reaction [33][34][35] because the upper (U) moiety HN¼ ¼C(NH 2 )À ÀN¼ ¼C(NH), 9b U , and the lower (L) moiety N(H)¼ ¼C(NH 2 )(NCNH), 9b L , resemble a diene and a dienophile, respectively. However, we could not locate a transition structure that formed bonds a and b in a synchronous fashion.…”
Section: (3)mentioning
confidence: 99%
“…A major problem of MOs is, however, that they are delocalized over the entire molecule and not necessarily suited to description of local events such as molecular interactions and chemical reactions. Hirao51–53 proposed a method for transforming delocalized fragment MOs into localized fragment MOs, namely, reactive bond orbitals (RBOs), and applied the method to the Diels–Alder reaction between butadiene and ethylene [Figure 11(a)] 53. For the description of such multicenter reactions, consideration of the orbital‐symmetry effect is essential.…”
Section: Introducing Mo Symmetry Into Vb Wave Functionsmentioning
confidence: 99%
“…The RBO approach utilizes localized fragment MOs that are localized onto the reaction center and effectively incorporates the orbital‐symmetry effect in VB‐like calculations. The RBO correlation diagram analysis showed that one‐electron transfer configurations [2 and 3 in Figure 11(b)] play important roles in the molecular interaction before the transition state, whereas the role of interfragment two‐electron transfer configuration [4 in Figure 11(b)] becomes dominant and significantly stabilizes the system after the transition state 53…”
Section: Introducing Mo Symmetry Into Vb Wave Functionsmentioning
confidence: 99%